PENGARUH PEMODERASI PERTUMBUHAN LABA TERHADAP HUBUNGAN ANTARA UKURAN PERUSAHAAN, DEBT TO EQUITY RATIO DENGAN PROFITABILITAS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI PT. BURSA EFEK JAKARTA - ENA MARBERYA, NI PUTU; SUARYANA, AGUNG (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 4 No 1 (2009), 2009)
One of parameter used to measure management performance is earnings. Porter (1980) reffer by Hamid (2001), defines growing company as those having high margin, earnings, and sales growth. Chang and Rhee (1990) and Adedeji (1998) state that company size affects profitability significanty. Big company will have ability to collect quict fund due to their easy access to capital market, and therefore earn higher profitability. On the other side, higher leverage will provide more fund to gain opportunities for companies to invest the fund into productive assets which at the end will increase profitability. This research is motivated by inconsistency results of previous researches on companies size and debt to equity ratio. Because of the inconsistency, this research incluse one moderating variable, namely earnings growth
Keywords: companies size, debt to equity ratio (DER), profitability, earnings growth.